Hydrophilic treatment agent, hydrophilic treatment method, method for producing hydrophilic aluminum-containing metal material

JP2026166731APending Publication Date: 2026-10-14NIHON PARKERIZING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025059876
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0016】 本発明の一実施形態によれば、長期間にわたり親水性、耐食性、及び抗菌性を保持することが可能な皮膜、特に流水や一般的な腐食環境に晒された後も多種類の細菌に対する抗菌性能を保持することが可能な皮膜を、アルミニウム含有金属材料の表面又は表面上に形成することができる親水化処理剤が提供される。当該親水化処理剤は、特に親水性の不足による水飛びや凝縮水の滞留による熱交換効率の低下、腐食による白粉飛散、冷媒流路の穴あきによる機能の損失、表面上での細菌の繁殖による悪臭の発生が課題となる熱交換器への適応性が高い。また、その他の幅広い用途にも適用することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166731000001
    Figure 2026166731000001
  • Figure 2026166731000002
    Figure 2026166731000002
  • Figure 2026166731000003
    Figure 2026166731000003
Patent Text Reader

Abstract

The present invention provides a hydrophilic treatment agent that can form a film on or on the surface of an aluminum-containing metal material that can maintain hydrophilicity, corrosion resistance, and antibacterial properties for a long period of time. [Solution] A hydrophilic treatment agent for aluminum-containing metal materials, comprising a water-soluble resin (A) having one or more functional groups of an amide group, a hydroxyl group, and an amino group; an organic antibacterial agent (B) having a quaternary ammonium group and a molecular weight of 1000 or less; a crosslinking agent (C); a surfactant (D); and water (E).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hydrophilizing treatment agent, a hydrophilizing treatment method using the same, and a method for producing a hydrophilized aluminum-containing metal material.

Background Art

[0002] Most heat exchangers having fins made of aluminum or aluminum alloy (hereinafter, aluminum and aluminum alloys may be collectively referred to as "aluminum material") are designed to maximize the surface area of the heat radiation part and the cooling part as much as possible in order to obtain excellent heat radiation efficiency or cooling efficiency in a limited space. For this reason, the gap between adjacent fins is extremely narrow. When these heat exchangers are used for cooling, moisture in the atmosphere condenses on the surfaces of the fins, forming a large amount of condensed water. If the condensed water is not discharged from the fin passages, it will cause clogging between the fins, increase ventilation resistance, and reduce the heat exchange efficiency.

[0003] If condensed water stays on the fin surfaces, corrosion of the aluminum material will be induced, a large amount of white powdery aluminum oxide will be generated on the fin surfaces, which will be scattered by the air flow of the air conditioner and cause discomfort to users. In addition, when condensed water stays on the fin surfaces, microorganisms such as bacteria are prone to propagate, resulting in the generation of offensive odors.

[0004] In order to suppress the retention of condensed water, a method of imparting hydrophilicity to the material surface is generally used. Since air conditioners are equipment used for many years, the surface of the aluminum material constituting the heat exchanger as a core component is required to have long-lasting hydrophilicity. In addition, in order to suppress the occurrence of corrosion and the propagation of bacteria, the surface of the aluminum material is required to have long-lasting antibacterial properties and corrosion resistance.

[0005] In recent years, surface treatments for heat exchangers used in automobiles and home appliance air conditioners have been required for the following reasons: corrosion resistance from the perspective of extending service life for resource conservation; hydrophilicity from the perspective of energy conservation by preventing increased airflow resistance due to clogging with condensation water; and antibacterial properties from the perspective of preventing unpleasant odors caused by bacterial growth, in response to the growing need for comfort.

[0006] For example, Patent Document 1 discloses an aluminum or aluminum alloy material having a second protective layer which is an organic film made up of a composition containing a first protective layer containing a metal compound, a chitosan derivative and a solubilizer, modified polyvinyl alcohol obtained by graft polymerization of a hydrophilic polymer onto the side chains of polyvinyl alcohol, and a water-soluble crosslinking agent.

[0007] Furthermore, Patent Document 2 discloses a metal surface treatment agent containing a copolymer having a quaternary ammonium structure and a water-soluble or water-dispersible resin in a specific ratio.

[0008] Furthermore, Patent Document 3 discloses a hydrophilic antifouling coating structure comprising a base layer, a glass-like coating layer provided on the base layer, and a betaine structure layer provided on the glass-like coating layer, characterized in that the glass-like coating layer and the betaine structure layer contain 1% by mass or more of silver ions. [Prior art documents] [Patent Documents]

[0009] [Patent Document 1] Japanese Patent Publication No. 2011-161876 [Patent Document 2] Japanese Patent Publication No. 2020-117777 [Patent Document 3] Japanese Patent Publication No. 2020-49901 [Overview of the Initiative] [Problems that the invention aims to solve]

[0010] According to Patent Document 1, an aluminum or aluminum alloy material is provided that can maintain hydrophilicity, high corrosion resistance, antibacterial properties, and deodorizing properties without deficiency over a long period of time. However, the antibacterial properties described in Patent Document 1 only refer to the antibacterial properties before and after the flow water test, and do not describe the antibacterial properties after exposure to a certain corrosive environment.

[0011] According to Patent Document 2, a novel metal surface treatment agent is provided that can form a film on or on the surface of a metal material that can maintain antibacterial properties. However, there is no mention of hydrophilicity or corrosion resistance. Furthermore, the antibacterial properties described in Patent Document 2 are only those before and after a flow water test, and there is no mention of antibacterial properties after exposure to a certain corrosive environment.

[0012] According to Patent Document 3, a highly durable, hydrophilic, antifouling coating structure with antibacterial properties is provided. However, the antibacterial properties after exposure to a certain corrosive environment are not described.

[0013] The present invention has been made to solve the above-mentioned conventional problems, and in one embodiment, aims to provide a hydrophilic treatment agent that can form a film on or on the surface of an aluminum-containing metal material that can maintain hydrophilicity, corrosion resistance, and antibacterial properties for a long period of time, and in particular a film that can maintain antibacterial properties against various types of bacteria even after exposure to flowing water and general corrosive environments. In another embodiment, the present invention aims to provide a hydrophilic treatment method using such a hydrophilic treatment agent. In yet another embodiment, the present invention aims to provide a method for producing a hydrophilized aluminum-containing metal material using such a hydrophilic treatment agent. [Means for solving the problem]

[0014] As a result of diligent research to solve the above problems, the inventors have found that a hydrophilic treatment agent containing an organic antibacterial agent having a quaternary ammonium group, a water-soluble resin, a crosslinking agent, and a surfactant can form a film on or on the surface of an aluminum-containing metal material that can impart hydrophilicity, corrosion resistance, and antibacterial properties over a long period of time, and have completed the present invention as illustrated below.

[0015] [Aspect 1] A hydrophilic treatment agent for aluminum-containing metal materials, comprising a water-soluble resin (A) having one or more functional groups of an amide group, a hydroxyl group, and an amino group; an organic antibacterial agent (B) having a quaternary ammonium group and a molecular weight of 1000 or less; a crosslinking agent (C); a surfactant (D); and water (E). [Aspect 2] The hydrophilizing agent for aluminum-containing metal materials according to Embodiment 1, wherein the water-soluble resin (A) comprises one or more of polyvinyl alcohol-based resins, polyethyleneimine-based resins, and polyacrylamide-based resins. [Aspect 3] Furthermore, the hydrophilizing agent for aluminum-containing metal materials according to embodiment 1 or 2, comprising a compound (F) having a nitrile group and an amino group. [Aspect 4] The hydrophilizing agent for aluminum-containing metal materials according to embodiment 3, wherein the mass ratio Fw / Aw of the solid content (Aw) of the water-soluble resin to the solid content (Fw) of the compound (F) is 0.05 to 0.31. [Aspect 5] A hydrophilic treatment agent for aluminum-containing metal materials according to any one of embodiments 1 to 4, wherein the surface tension of a 0.1% by mass aqueous solution of the surfactant (D) measured by the Wilhelmy method at 25°C is 20 to 65 mN / m, and the mass ratio Bw / Dw of the solid content (Bw) of the organic antibacterial agent (B) to the solid content (Dw) of the surfactant (D) is 0.12 to 30.00. [Aspect 6] The hydrophilizing treatment agent for aluminum-containing metallic materials according to any one of Aspects 1 to 5, wherein the mass ratio Bw / Aw of the solid content (Bw) of the organic antibacterial agent (B) to the solid content (Aw) of the water-soluble resin (A) is 0.005 to 1.020, and the mass ratio Cw / Aw of the solid content (Cw) of the crosslinking agent (C) to the solid content (Aw) of the water-soluble resin (A) is 0.0262 to 2.04. [Aspect 7] The hydrophilizing treatment agent for aluminum-containing metallic materials according to any one of Aspects 1 to 6, wherein the organic antibacterial agent (B) comprises a compound having an aromatic ring. [Aspect 8] The hydrophilizing treatment agent for aluminum-containing metallic materials according to Aspect 7, wherein the compound having an aromatic ring has a benzene ring. [Aspect 9] The hydrophilizing treatment agent for aluminum-containing metallic materials according to any one of Aspects 1 to 8, wherein among the quaternary ammonium salts constituting the organic antibacterial agent (B), when carbon and hydrogen directly bonded to carbon are regarded as hydrophobic sites, and all other elements except the counter anion are regarded as hydrophilic sites, the ratio [L-Aw] / [Aw] of the total atomic weight [L-Aw] of the hydrophobic sites to the total molecular weight [Aw] excluding the counter anion is in the range of 0.75 to 0.99. [Aspect 10] The hydrophilizing treatment agent for aluminum-containing metallic materials according to any one of Aspects 1 to 9, wherein the crosslinking agent (C) comprises a water-soluble metal compound. [Aspect 11] The hydrophilizing treatment agent for aluminum-containing metallic materials according to any one of Aspects 1 to 9, wherein the crosslinking agent (C) comprises a compound having an anionic functional group with a valence of 2 or more and 4 or less. [Aspect 12] The hydrophilizing treatment agent for aluminum-containing metallic materials according to any one of Aspects 1 to 9, wherein the crosslinking agent (C) comprises a water-soluble metal compound and a compound having an anionic functional group with a valence of 2 or more and 4 or less. [Aspect 13] A method for hydrophilizing an aluminum-containing metal material, comprising a bringing step of bringing the hydrophilization treating agent according to any one of aspects 1 to 12 into contact with or onto the surface of the aluminum-containing metal material, and a drying step of drying the hydrophilization treating agent after the bringing step. [Aspect 14] A method for producing a hydrophilized aluminum-containing metal material, comprising a bringing step of bringing the hydrophilization treating agent according to any one of aspects 1 to 12 into contact with or onto the surface of an aluminum-containing metal material, and a drying step of drying the hydrophilization treating agent after the bringing step. [Effects of the Invention]

[0016] According to one embodiment of the present invention, there is provided a hydrophilization treating agent capable of forming, on or onto the surface of an aluminum-containing metal material, a coating film that can retain hydrophilicity, corrosion resistance, and antibacterial properties over a long period of time, particularly a coating film that can retain antibacterial performance against a wide variety of bacteria even after being exposed to flowing water or a general corrosive environment. The hydrophilization treating agent has high adaptability to heat exchangers for which problems such as reduction in heat exchange efficiency due to water splashing caused by insufficient hydrophilicity or stagnation of condensed water, white powder scattering due to corrosion, loss of function due to perforation of refrigerant flow paths, and generation of offensive odor due to bacterial growth on the surface are concerns. It can also be applied to a wide range of other uses.

[0017] Therefore, the hydrophilized aluminum-containing metal material produced using the hydrophilization treating agent according to one embodiment of the present invention can provide a comfortable indoor environment over a long period of time when applied to, for example, a heat exchanger for an air conditioner. [Modes for Carrying Out the Invention]

[0018] Hereinafter, a hydrophilization treating agent according to one embodiment of the present invention, a hydrophilization treatment method using the same, and a method for producing a hydrophilized aluminum-containing metal material will be described.

[0019] [1. Hydrophilization Treating Agent] The hydrophilic treatment agent according to this embodiment comprises a water-soluble resin (A) having one or more functional groups of amide, hydroxyl, and amino groups; an organic antibacterial agent (B) having a quaternary ammonium group and a molecular weight of 1000 or less; a crosslinking agent (C); a surfactant (D); and water (E). This hydrophilic treatment agent can form a film on or on the surface of an aluminum-containing metal material that can maintain hydrophilicity, corrosion resistance, and antibacterial properties for a long period of time. Each component will be described in detail below.

[0020] <Water-soluble resin (A)> The water-soluble resin (A) is characterized by having one or more functional groups, including an amide group (-CONH2), a hydroxyl group (-OH), and an amino group (primary, secondary, tertiary, and quaternary amino groups). There are no other conditions for the water-soluble resin (A), but for superior effectiveness, it is preferable to use, for example, a polyvinyl alcohol-based resin, a polyethyleneimine-based resin, or a polyacrylamide-based resin. Furthermore, it is preferable that the solubility of the water-soluble resin (A) in water at 25°C is 0.1 g / L or higher. The water-soluble resin (A) may be a homopolymer, a modified product obtained by modifying the side chains of the homopolymer with other compounds, or a copolymer obtained by combining two or more of these homopolymers or modified products. The water-soluble resin (A) may be used alone or in combination of two or more types.

[0021] From the viewpoint of improving durability, the lower limit of the weight-average molecular weight of the water-soluble resin (A) is preferably 1,000 or more, more preferably 10,000 or more, and even more preferably 100,000 or more. There is no particular upper limit set for the weight-average molecular weight of the water-soluble resin (A), but in the range of commonly available materials it is 5,000,000 or less, typically 2,500,000 or less, and more typically 1,000,000 or less. The weight-average molecular weight of the water-soluble resin (A) is preferably, for example, 1,000 to 5,000,000, more preferably 10,000 to 2,500,000, and even more preferably 100,000 to 1,000,000. The weight-average molecular weight of the water-soluble resin (A) can be determined by measuring it by GPC (gel permeation column chromatography) and converting it to polystyrene.

[0022] In terms of superior effectiveness, the mass ratio [Bw / Aw] of the solid content (Bw) of the organic antibacterial agent (B) to the solid content (Aw) of the water-soluble resin (A) in the hydrophilic treatment agent according to this embodiment is preferably in the range of 0.001 to 1.0420, and more preferably in the range of 0.005 to 1.020. If the ratio of the organic antibacterial agent (B) is too high, the hydrophilicity is easily impaired because the antibacterial agent has relatively high hydrophobicity, and corrosion resistance is easily impaired because the amount of halide ions such as chloride ions that the antibacterial agent has as counterions increases. If the ratio of the organic antibacterial agent (B) is too low, the antibacterial effect will be insufficient.

[0023] In terms of superior effectiveness, the mass ratio [Cw / Aw] of the solid content of the crosslinking agent (C) to the solid content of the water-soluble resin (A) in the hydrophilic treatment agent according to this embodiment is preferably in the range of 0.01 to 2.422, and more preferably in the range of 0.0262 to 2.04. If the ratio of the crosslinking agent (C) is too high, the hydrophilic functional groups (amide groups, hydroxyl groups, and amino groups) contained in the water-soluble resin are excessively reduced by the crosslinking reaction during film formation, which tends to impair hydrophilicity. If the ratio of the crosslinking agent (C) is too low, the crosslinking reaction with the water-soluble resin during film formation is insufficient, which impairs the durability of the film and tends to reduce the persistence of corrosion resistance and antibacterial properties.

[0024] <Organic antibacterial agent (B)> The organic antimicrobial agent (B) is characterized by having a quaternary ammonium group and a molecular weight of 1000 or less, preferably 500 or less. Therefore, the organic antimicrobial agent (B) is generally provided in the form of a quaternary ammonium salt with a halide such as Cl or Br. There are no other conditions for the organic antimicrobial agent (B), but in terms of superior efficacy, compounds having aromatic rings such as a benzene ring, pyridine ring, imidazole ring, pyrrole ring, pyrazole ring, pyridazine ring, pyrimidine ring, or pyrazine ring are preferred, and compounds having a benzene ring are more preferred. Examples of organic antimicrobial agents (B) include benzethonium chloride, cetyltrimethylammonium bromide, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, 3,3′-[tetramethylenebis(oxymethylene)]bis(1-decylpyridinium)·dibromide, 4,4'-(tetramethylenedicarbonyldiamino)bis(1-decylpyridinium bromide), benzalkonium chloride, didecyldimethylammonium chloride, N,N'-hexamethylenebis(4-carbonyl-1-decylpyridinium bromide), N-decyl-N-isodecyl- It is preferable to use N,N'-dimethylammonium chloride, cetylpyridinium chloride, etc., and among these, benzethonium chloride, cetyltrimethylammonium bromide, 3,3'-[tetramethylenebis(oxymethylene)]bis(1-decylpyridinium)·dibromide, 4,4'-(tetramethylenedicarbonyldiamino)bis(1-decylpyridinium bromide), benzalkonium chloride, didecyldimethylammonium chloride, N-decyl-N-isodecyl-N,N'-dimethylammonium chloride, and cetylpyridinium chloride are particularly preferred. One type of organic antimicrobial agent (B) may be used alone, or two or more types may be used in combination. The molecular weight of the organic antimicrobial agent can be calculated from the atomic weight of each element if it is a low molecular weight compound with a known chemical structure, and if it is a high molecular weight compound with an unknown chemical structure, it can be measured by GPC (gel permeation column chromatography) and converted to polystyrene.

[0025] Since antimicrobial agents having quaternary ammonium groups exhibit superior antimicrobial properties the higher their hydrophobicity, it is preferable that they contain a greater number of hydrophobic moieties. Specifically, in the quaternary ammonium salt constituting the organic antimicrobial agent (B), when carbon and hydrogen directly bonded to carbon are considered as hydrophobic moieties and all other elements excluding counter anions are considered as hydrophilic moieties, the ratio [L-Aw] / [Aw] of the total atomic weight of the hydrophobic moieties [L-Aw] to the total molecular weight excluding counter anions [Aw] is preferably in the range of 0.70 to 0.99, and more preferably in the range of 0.75 to 0.99.

[0026] <Crosslinking agent (C)> The crosslinking agent (C) is not particularly limited, and for example, organic crosslinking agents and water-soluble metal compounds can be used. Specific examples of organic crosslinking agents include epoxy crosslinking agents, blocked isocyanate crosslinking agents, carboxylic acid crosslinking agents such as citric acid, tartaric acid, maleic acid, and butanetetracarboxylic acid, phosphonic acid crosslinking agents such as phosphonic acid and nitrilotrismethylenephosphonic acid, and amine crosslinking agents. Specific examples of water-soluble metal compounds include organotitanium compounds such as diisopropoxytitanium bis(triethanolamine)titanium; chromium-containing compounds such as chromium(III) sulfate and chromium(III) nitrate; inorganic zirconium-containing compounds such as zirconium ammonium carbonate and hexafluorozirconium acid; inorganic titanium-containing compounds such as hexafluorotitanium acid and ammonium titanium fluoride; and inorganic crosslinking agents such as sodium metavanadate. The crosslinking agent (C) may be used alone or in combination of two or more types. The crosslinking agent reacts with specific functional groups of the water-soluble resin during film formation, improving the water resistance of the film and enhancing its hydrophilicity, corrosion resistance, and the persistence of its antibacterial properties. Among these, the use of at least one of a water-soluble metal compound and a compound having an anionic functional group between divalent and tetravalent is preferable because it further improves hydrophilicity. Furthermore, the compound having an anionic functional group between divalent and tetravalent is even more preferable because it further improves the durability of the antibacterial agent through ionic bonding with the cationic antibacterial agent, thereby improving the persistence of its antibacterial properties. In particular, it is preferable to use both a water-soluble metal compound and a compound having an anionic functional group between divalent and tetravalent.

[0027] <Surfactant (D)> As surfactant (D), cationic, anionic, amphoteric, and nonionic surfactants can be used. Examples include cationic surfactants such as alkylamine salts and alkyltrimethylammonium halides; anionic surfactants such as alkyl sulfonic acid esters, polyoxyethylene alkylphenyl ether sulfates, sodium dodecyldiphenyl ether disulfonate, and sodium dodecyl sulfate; amphoteric surfactants such as alkylaminopropionates and alkyldimethyl betaine; and nonionic surfactants such as polyoxyethylene alkylphenyl ethers, polyoxyalkylene fatty acid esters, fatty acid glycerol esters, sorbitan fatty acid esters, polyoxyethylene glycerol fatty acids, and polyoxyethylene propylene glycol fatty acid esters. Surfactant (D) may be used alone or in combination of two or more. Among these, it is preferable to use surfactant (D) whose surface tension at 25°C of a 0.1% by mass aqueous solution, measured using the Wilhelmy method, is 20 to 65 mN / m, and it is more preferable to use surfactant (E) whose surface tension is 30 to 50 mN / m. Furthermore, in the hydrophilic treatment agent according to this embodiment, the mass ratio [Bw / Dw] of the solid content (Bw) of the organic antibacterial agent (B) to the solid content (Dw) of the surfactant (D) is preferably in the range of 0.1 to 50.00, more preferably in the range of 0.12 to 30.00, and even more preferably in the range of 0.46 to 24.15. By using the surfactant (D), it is possible to stabilize the organic antibacterial agent (B) in aqueous solution and control the orientation of the organic antibacterial agent (B) during the film formation process, thereby contributing to the expression of hydrophilicity and antibacterial properties. If the amount of surfactant is small, it becomes unstable in aqueous solution and precipitation is likely to occur. Also, if the antibacterial properties become excessively concentrated on the film surface, hydrophilicity is likely to be impaired. If the amount of surfactant is too large, the antibacterial properties tend to decrease as the amount of antibacterial agent present on the film surface decreases.

[0028] <Water(E)> As water (E), industrial water or deionized water may be used. For example, water with a purity of 20 μS / cm or less, preferably 5 μS / cm or less, in electrical conductivity at 25°C can be suitably used. There are no particular restrictions on the water (E) content, but from the viewpoint of ensuring that the various components A to F exist stably in aqueous solution and ease of application to aluminum-containing metal materials, it is preferable to adjust the amount of water (E) so that the total solid content concentration in the hydrophilizing agent is preferably 10 to 200 g / L, more preferably 20 to 150 g / L, and even more preferably 30 to 100 g / L.

[0029] <Compounds containing nitrile and amino groups (F)> The hydrophilic treatment agent preferably further contains a compound (F) having a nitrile group and an amino group. Compound (F) is not particularly limited as long as it has a nitrile group and an amino group and is different from the water-soluble resin (A). Examples include cyanamide, aminoacetonitrile, 3-aminopropionitrile, dicyandiamide, 3-aminocrotononitrile, 2-amino-1,1,3-tricyano-1-propene, 2-aminobenzonitrile, 3-aminobenzonitrile, 4-aminobenzonitrile, 2-aminobenzylcyanide, 4-aminobenzylcyanide, 2-amino-5-bromobenzonitrile, 2-amino-5-nitrobenzonitrile, 4-amino-3-bromobenzonitrile, 2-amino-4-chlorobenzonitrile, 2-amino-5-chlorobenzonitrile, 2-amino-4,5-dicyano-1H-imidazole, 4-(aminomethyl)benzonitrile, and the like. The upper limit of the molecular weight of compound (F) is preferably 1000 or less, more preferably 800 or less, and particularly preferably 500 or less. The lower limit of the molecular weight of compound (F) is preferably 40 or more, more preferably 55 or more, and even more preferably 80 or more. Therefore, the molecular weight of compound (F) is preferably, for example, 40 to 1000, more preferably 55 to 800, and even more preferably 80 to 500. Furthermore, it is preferable that compound (F) is not a polymer having a repeating structure. Compound (F) having nitrile groups and amino groups can improve the adhesion between the substrate and the film, and further improve corrosion resistance. In addition, the mass ratio Fw / Aw of the solid content of the water-soluble resin to the solid content of compound (F) (Fw) in the hydrophilic treatment agent according to this embodiment is preferably in the range of 0.005 to 0.31, more preferably in the range of 0.01 to 0.25, and even more preferably in the range of 0.1 to 0.2.

[0030] <Other> The hydrophilic treatment agent according to this embodiment may consist only of a water-soluble resin (A) having one or more functional groups of an amide group, a hydroxyl group, and an amino group; an organic antibacterial agent (B) having a quaternary ammonium group and a molecular weight of 1000 or less; a crosslinking agent (C); a surfactant (D); and water (E); however, it may also contain other components. Examples of other components include a compound (F) having a nitrile group and an amino group; a water-soluble organic solvent; and an antibacterial agent that does not have a quaternary ammonium group.

[0031] In terms of superior effectiveness, the hydrophilic treatment agent according to this embodiment preferably satisfies the following conditions: the solid content (Aw) of the water-soluble resin (A), the solid content (Bw) of the organic antibacterial agent (B) having a quaternary ammonium group and a molecular weight of 1000 or less, the solid content (Cw) of the crosslinking agent (C), and the solid content (Dw) of the surfactant (D). <Condition 1 (mass ratio)> 0.15≦Aw / (Aw+Bw+Cw+Dw)≦0.98 0.001≦Bw / (Aw+Bw+Cw+Dw)≦0.5 0.01≦Cw / (Aw+Bw+Cw+Dw)≦0.84 0.01 ≤ Dw / (Aw + Bw + Cw + Dw) ≤ 0.3 <Condition 2 (mass ratio)> 0.2 ≤ Aw / (Aw + Bw + Cw + Dw) ≤ 0.8 0.005≦Bw / (Aw+Bw+Cw+Dw)≦0.25 0.05≦Cw / (Aw+Bw+Cw+Dw)≦0.75 0.02≦Dw / (Aw+Bw+Cw+Dw)≦0.25 <Condition 3 (mass ratio)> 0.25 ≤ Aw / (Aw + Bw + Cw + Dw) ≤ 0.6 0.01 ≤ Bw / (Aw + Bw + Cw + Dw) ≤ 0.1 0.1 ≤ Cw / (Aw + Bw + Cw + Dw) ≤ 0.65 0.03 ≤ Dw / (Aw + Bw + Cw + Dw) ≤ 0.2

[0032] In terms of superior effectiveness when a compound (F) having a nitrile group and an amino group is included, the hydrophilic treatment agent according to this embodiment preferably satisfies the following conditions 4, more preferably satisfies condition 5, and even more preferably satisfies condition 6. <Condition 4 (mass ratio)> 0.005≦Fw / (Aw+Bw+Cw+Dw)≦0.255 <Condition 5 (mass ratio)> 0.01≦Fw / (Aw+Bw+Cw+Dw)≦0.15 <Condition 6 (mass ratio)> 0.025≦Fw / (Aw+Bw+Cw+Dw)≦0.115

[0033] In this embodiment, the hydrophilic treatment agent has a total mass ratio of 60% by mass or more, typically 70% by mass or more, and more typically 80% by mass or more, of the solid content of the water-soluble resin (A) (Aw), the solid content of the organic antibacterial agent (B) having a quaternary ammonium group and a molecular weight of 1000 or less (Bw), the solid content of the crosslinking agent (C) (Cw), and the solid content of the surfactant (D) (Dw) relative to the total solid content.

[0034] <Method for manufacturing hydrophilic treatment agent> The hydrophilic treatment agent according to this embodiment can be manufactured, for example, by mixing a predetermined amount of a water-soluble resin (A), an organic antibacterial agent (B), a crosslinking agent (C), a surfactant (D), and other components as needed, with water (E). Furthermore, the inclusion of impurities such as organic solvents in the hydrophilic treatment agent is permissible.

[0035] [2. Method for hydrophilizing aluminum-containing metal materials and method for manufacturing hydrophilic aluminum-containing metal materials] According to one embodiment of the present invention, a hydrophilic treatment method is provided, comprising a contact step of bringing a hydrophilic treatment agent according to the above embodiment into contact with the surface or surface of an aluminum-containing metal material, and a drying step of drying the hydrophilic treatment agent after the contact step. This hydrophilic treatment method makes it possible to form a film on the surface or surface of an aluminum-containing metal material that can maintain antibacterial performance. Accordingly, according to another embodiment of the present invention, a method for producing a hydrophilic aluminum-containing metal material is provided, comprising a contact step of bringing a hydrophilic treatment agent according to the above embodiment into contact with the surface or surface of an aluminum-containing metal material, and a drying step of drying the hydrophilic treatment agent after the contact step. Note that a degreasing step and / or a chemical conversion step may be performed on the aluminum-containing metal material before the contact step according to this embodiment.

[0036] <Aluminum-containing metal materials> The type, shape, and structure of the aluminum-containing metal material are not particularly limited. Examples of aluminum-containing metal materials include aluminum and aluminum alloys of the 1000 series (pure Al), 2000 series (Al-Cu alloy), 3000 series (Al-Mn alloy), 4000 series (Al-Si alloy), 5000 series (Al-Mg alloy), and 6000 series (Al-Mg-Si alloy) as defined in JIS H4100:2015. Furthermore, the aluminum-containing metal material can be provided in forms such as castings, die-cast materials, or clad materials.

[0037] <Contact method> Methods for bringing the hydrophilic treatment agent into contact with an aluminum-containing metal material include, but are not limited to, spraying, immersion, roll coating, bar coating, curtain coating, spin coating, or combinations thereof. The contact temperature and contact time are set appropriately depending on the composition and concentration of the hydrophilic treatment agent, but typically the contact temperature is in the range of 0°C to 50°C, and the contact time is in the range of 1 second to 300 seconds.

[0038] <Drying process> The drying method is not particularly limited, and known drying equipment can be used, such as batch-type drying ovens, continuous-type hot air circulation drying ovens, conveyor-type hot air drying ovens, and electromagnetic induction heating ovens using IH heaters. The drying temperature and drying time are set appropriately depending on the type of aluminum-containing metal material and the composition or amount of the hydrophilizing agent that comes into contact with it, but usually the drying temperature is in the range of 120°C to 200°C, and the drying time is in the range of 2 seconds to 1800 seconds.

[0039] <Degreasing process> Any degreasing method is acceptable as long as it can remove oils and dirt. Examples include known methods using solvent degreasing, alkaline or acidic degreasing agents, etc. If a contact process or chemical conversion process is performed after the degreasing process, the aluminum-containing metal material may or may not be washed with water after the degreasing process but before the contact process or chemical conversion process. If water washing is performed, the aluminum-containing metal material may or may not be dried afterward.

[0040] <Chemical treatment process> The chemical conversion treatment process is not particularly limited as long as it is a process that forms a chemical conversion film, and examples include a zirconium chemical conversion treatment process, a titanium chemical conversion treatment process, a hafnium chemical conversion treatment process, a phosphate chlorination treatment process, a chromate chemical conversion treatment process, etc. After the chemical conversion treatment process but before the contact process, the aluminum-containing metal material may or may not be washed with water. If washing with water is performed, the aluminum-containing metal material may or may not be dried afterward. In the case of a phosphate chlorination treatment process using zinc phosphate as the chemical conversion treatment process, a surface adjustment treatment process for the aluminum-containing metal material may be performed between the degreasing process and the phosphate chlorination treatment process for the purpose of improving the reactivity of the phosphate chlorination treatment. Known methods can be used as this surface adjustment treatment method.

[0041] <Chemical treatment agent> The chemical conversion treatment process is carried out by bringing a chemical conversion agent into contact with the surface of a metal material or onto its surface. Examples of chemical conversion agents include, but are not limited to, zirconium chemical conversion agents, titanium chemical conversion agents, hafnium chemical conversion agents, phosphate chloride chemical conversion agents, chromate chemical conversion agents, etc. Contact with the chemical conversion agent can be carried out by known methods, such as immersion treatment, spray treatment, pouring treatment, or combinations thereof, but is not limited to these. The temperature or contact time of the chemical conversion agent in each chemical conversion treatment process can be appropriately set according to the type of chemical conversion treatment process, the concentration of the chemical conversion agent, etc.

[0042] <coating> The mass of the film formed on or on the surface of an aluminum-containing metal material by the hydrophilizing agent is not particularly limited as long as the performance of the present invention is achieved, but for example, 0.1 g / m 2 More than 2.0g / m 2 Preferably, it is within the following range: 0.3 g / m 2 More than 1.5g / m 2 It is more preferable that the range be within the following: [Examples]

[0043] The present invention will be described in more detail using examples and comparative examples. However, the present invention is not limited to the following examples.

[0044] <Material> As materials for manufacturing the hydrophilic treatment agent, the following were prepared as shown in Table 1: a water-soluble resin (A), an antibacterial agent (B), a crosslinking agent (C), a surfactant (D), water (E), and a compound (F) having a nitrile group and an amino group. In Table 1, the molecular weights of each polymer refer to the weight-average molecular weight in polystyrene terms, measured by GPC (gel permeation column chromatography). The surface tension of surfactant (D) refers to the surface tension of a 0.1% by mass aqueous solution at 25°C, measured using the Wilhelmy method.

[0045] [Table 1]

[0046] <Preparation of hydrophilic treatment agent> The hydrophilic treatment agents for Examples 1-48 and Comparative Examples 1-5 shown in Table 2 were prepared by mixing a water-soluble resin (A), an antibacterial agent (B), a crosslinking agent (C), a surfactant (D), and a compound having a nitrile group and an amino group (F) in that order with water (E) so that the total solid content concentration was 50 g / L.

[0047] [Table 2-1]

[0048] [Table 2-2]

[0049] <Creation of evaluation samples> An aluminum plate (A1050, thickness: 0.6 mm) was used as the test material and degreased by immersion in an alkaline degreasing agent [Fine Cleaner 315E (manufactured by Nippon Parkerizing Co., Ltd.) dissolved in water at a mass concentration of 2%] at 60°C for 2 minutes. After that, the test material was washed with water.

[0050] The test specimens, which had been degreased and washed with water, were subjected to a chemical conversion treatment by immersion at 60°C for 2 minutes in a zirconium-based chemical conversion agent [Palcoat 3762 (manufactured by Nippon Parkerizing Co., Ltd.) dissolved in water to a mass concentration of 5% and adjusted to pH 4.0]. After the chemical conversion treatment, the test specimens were washed with water.

[0051] Test materials with a chemical conversion coating formed by chemical conversion treatment were immersed in each hydrophilic treatment agent (hydrophilic treatment agents of Examples 1-48 and Comparative Examples 1-5) at 25°C for 10 seconds, and then heated and dried in a forced-air dryer at 150°C for 6 minutes to produce test materials with a coating (evaluation samples No. 1-53).

[0052] <Method for evaluating initial hydrophilicity> One drop of water was placed on the surface of the evaluation sample prepared as described above (hereinafter referred to as the "initial sample"), and the contact angle immediately after dropping was measured using a contact angle measuring device. The initial hydrophilicity was then evaluated according to the following evaluation criteria. (Evaluation Criteria) A: Less than 10° B: 10° to less than 20° C: 20° to less than 30° D: 30° or more

[0053] <Method for evaluating hydrophilicity after durability> After drying the surface of the evaluation sample (hereinafter referred to as the "water-immersion sample") that had been immersed in deionized water for 96 hours, one drop of water was dropped onto it, and the contact angle immediately after dropping was measured using a contact angle measuring device. The hydrophilicity after durability was then evaluated according to the following evaluation criteria. (Evaluation Criteria) A: Less than 25° B: 25° or more and less than 30° C: 30° to less than 40° D: 40° or more

[0054] <Method for evaluating corrosion resistance: Wet test> After exposure for 340 hours in a wet testing chamber (CT-3: manufactured by Suga Test Instruments Co., Ltd.) maintained at a temperature of 65±1℃ and a relative humidity of 95% or higher, the area percentage (%) of discoloration that occurred on the surface of the evaluation sample (hereinafter referred to as the "post-wet testing sample") was calculated, and the corrosion resistance was evaluated according to the following evaluation criteria. (Evaluation Criteria) A: No discoloration B: Less than 25% discoloration C: Discoloration 25% to less than 50% D: Discoloration of 50% or more

[0055] <Method for evaluating corrosion resistance: Salt spray test (SST)> Based on the salt spray test method (JIS-Z-2371:2015), neutral salt water was sprayed for 480 hours, and the area percentage (%) of discoloration that occurred on the surface of the evaluation sample was calculated. Corrosion resistance was then evaluated according to the following evaluation criteria. (Evaluation Criteria) A: No discoloration B: Less than 25% discoloration C: Discoloration 25% to less than 50% D: Discoloration of 50% or more

[0056] <Method for evaluating corrosion resistance: SWAAT test (Sea Water ACIDIFIED Test)> A SWAAT test (ASTM G85 Annex 2) was performed. The evaluation cycle was set to 120 cycles. The area percentage (%) of discoloration that occurred on the surface of the evaluation sample was calculated, and the corrosion resistance was evaluated according to the following evaluation criteria. (Evaluation Criteria) A: No discoloration B: Less than 25% discoloration C: Discoloration 25% to less than 50% D: Discoloration of 50% or more

[0057] <Method for evaluating antibacterial properties> The antibacterial activity of evaluation samples 1 to 45 was evaluated according to the evaluation method described in ISO 22196:2011 (Film Contact Method). The bacteria used were Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Bacillus subtilis, respectively. Antibacterial performance was evaluated based on the following criteria, using the formula [Percentage Reduction of Target Bacteria (%) = 100 - Y / Z × 100] to calculate the percentage reduction of target bacteria. In the formula, Y represents the number of colonies formed when the evaluation sample was added and cultured, and Z represents the number of colonies formed when the evaluation sample was not added and cultured. Evaluation samples 1-41 consisted of the initial sample, the sample after water immersion, and the sample after the wet test, as described above. (Evaluation Criteria) A: There are four bacterial species with a reduction rate of 99.9% or more. B: Four species showed a reduction rate of 99% or more. C: Three species showed a reduction rate of 99% or more. D: Two species showed a reduction rate of 99% or more. E: One bacterial species with a reduction rate of 99% or more. F: Fewer than one bacterial species with a reduction rate of 99% or more.

[0058] Table 3 shows the hydrophilicity evaluation results, corrosion resistance evaluation results, and antibacterial evaluation results for each evaluation sample. A score of B or higher was considered a passing grade. Table 4 details the reduction rate of each bacterium. The evaluation criteria are as follows: ◎: Reduction rate of 99.9% or more ○: Decrease rate of 99% or more but less than 99.9% ×: Less than 99%

[0059] [Table 3]

[0060] [Table 4]

Claims

1. A hydrophilic treatment agent for aluminum-containing metal materials, comprising: a water-soluble resin (A) having one or more functional groups of an amide group, a hydroxyl group, and an amino group; an organic antibacterial agent (B) having a quaternary ammonium group and a molecular weight of 1000 or less; a crosslinking agent (C); a surfactant (D); and water (E).

2. The hydrophilizing agent for aluminum-containing metal materials according to claim 1, wherein the water-soluble resin (A) comprises one or more of polyvinyl alcohol-based resins, polyethyleneimine-based resins, and polyacrylamide-based resins.

3. Furthermore, the hydrophilizing agent for aluminum-containing metal materials according to claim 1, comprising a compound (F) having a nitrile group and an amino group.

4. The hydrophilizing agent for aluminum-containing metal materials according to claim 3, wherein the mass ratio Fw / Aw of the solid content of the water-soluble resin to the solid content (Fw) of the compound (F) is 0.005 to 0.

31.

5. The hydrophilizing agent for aluminum-containing metal materials according to claim 1, wherein the surface tension of a 0.1% by mass aqueous solution of the surfactant (D), measured using the Wilhelmy method, at 25°C is 20 to 65 mN / m, and the mass ratio Bw / Dw of the solid content (Bw) of the organic antimicrobial agent (B) to the solid content (Dw) of the surfactant (D) is 0.12 to 30.

00.

6. The hydrophilizing agent for aluminum-containing metal materials according to claim 1, wherein the mass ratio Bw / Aw of the solid content (Bw) of the organic antibacterial agent (B) to the solid content (Aw) of the water-soluble resin (A) is 0.005 to 1.020, and the mass ratio Cw / Aw of the solid content (Cw) of the crosslinking agent (C) to the solid content (Aw) of the water-soluble resin (A) is 0.0262 to 2.

04.

7. The hydrophilic treatment agent for aluminum-containing metal materials according to claim 1, wherein the organic antibacterial agent (B) comprises a compound having an aromatic ring.

8. The hydrophilizing agent for aluminum-containing metal materials according to claim 7, wherein the compound having the aromatic ring has a benzene ring.

9. The hydrophilizing agent for aluminum-containing metal materials according to claim 1, wherein, in the quaternary ammonium salt constituting the organic antibacterial agent (B), when carbon and hydrogen directly bonded to carbon are considered as hydrophobic sites and other elements excluding counter anions are considered as hydrophilic sites, the ratio [L-Aw] / [Aw] of the total atomic weight of the hydrophobic sites [L-Aw] to the total molecular weight excluding counter anions [Aw] is in the range of 0.75 to 0.

99.

10. The hydrophilizing agent for aluminum-containing metal materials according to claim 1, wherein the crosslinking agent (C) comprises a water-soluble metal compound.

11. The hydrophilizing agent for aluminum-containing metal materials according to claim 1, wherein the crosslinking agent (C) comprises a compound having an anionic functional group of divalent to tetravalent or less.

12. The hydrophilizing agent for aluminum-containing metal materials according to claim 1, wherein the crosslinking agent (C) comprises a water-soluble metal compound and a compound having an anionic functional group of divalent to tetravalent or less.

13. A method for hydrophilizing an aluminum-containing metal material, comprising a contact step of bringing a hydrophilizing agent described in any one of claims 1 to 12 into contact with the surface or onto the surface of an aluminum-containing metal material, and a drying step of drying the hydrophilizing agent after the contact step.

14. A method for producing a hydrophilized aluminum-containing metal material, comprising a contact step of bringing a hydrophilizing agent according to any one of claims 1 to 12 into contact with the surface or onto the surface of an aluminum-containing metal material, and a drying step of drying the hydrophilizing agent after the contact step.

Citation Information

Patent Citations

  • Aluminum or aluminum alloy material having surface-treated film and method of heat treatment thereof

    JP2011161876A

  • Hydrophilic antifouling coat structure having antibacterial property, method for forming the same, and measurement device

    JP2020049901A

  • Metal surface treatment agent, metal material having coating film and method for manufacturing the same

    JP2020117777A